Effect of excimer laser on microbiological organisms - KEATES, R. H; DRAGO, P. C; ROTHCHILD, E. J (Ophthalmic surgery, 1988)
The effect of radiation emitted from an excimer laser filled with argon fluoride gas at 193 nm on Serratia marcescens, Pseudomonas aeruginosa, Staphylococcus aureus, streptococcus faecalis, Hemophilus influenzae, Candida albicans, and Aspergillus niger (collectively labeled "the microorganisms") was examined. Colonies were subjected to a variable number of radiation pulses from the excimer laser applied after a 36-hour period of incubation at 37 degrees C, at which time the colonies were fully grown and showed no viability. The lack of viability was confirmed with a subculture from each area that received radiation; all subcultures were negative. The characteristics of the radiation paralleled those used by Serdavic, Darrell, Krueger, et al in 1985.(1) This radiation treatment is believed to be within a therapeutic range, which suggests that the excimer laser, pending further investigation, may be useful in the treatment of corneal infections.